Sensitization to grass allergens: Phl p1, Phl p5 and Phl p7 Phl p12 in Adult and Children Patients in Beja (Southern Portugal) - Almeida, Elsa (2019)
Background In Portugal, the pollen types most implicated in respiratory allergy are grasses, olive and parietaria. The knowledge of sensitizations to molecular allergens in children and adults can contribute to better diagnosis and treatment of this pathology. Methods ImmunoCAP singleplex technology was used for molecular allergens and Phadia 250® automatic equipment. g205 (Phl p1); g215 (Phl p5b); g210 (Phl p7); and g212 (Phl p12) allergen determinations were made in 45 patients with positive grass sensitization tests. Results The majority of patients are sensitized to Phl p1 (91%) and Phl p1+/Phl p5−/Phl p7−/Phl p12− was the most dominant profile (40%). In the adult group, the IgE averages for Phl p1 were approximately 10.46, while they were 8.43 for Phl p5, 0.69 for Phl p7, and 0.06 for Phl p12. In the child group, these values were higher: 22.49, 20.23, 3.89, and 0.35, respectively. For allergens Phl p1, Phl p5, and Phl p7, these differences between the child and adult population were not statistically significant (p = 0.754, p = 0.806 and p = 0.102, respectively), but for Phl p12, a statistically significant difference (p = 0.018) was observed. Conclusions IgE antibodies Phl p1 is the most important allergic marker and sensitivities caused by Phl p12 give rise to higher IgE values in children.